Designing new synthetic materials for use in the pelvic floor: what is the problem with the existing polypropylene materials?. Issue 4 (July 2019) - Roman, Sabiniano; Mangir, Naside; MacNeil, Sheila
Abstract : Purpose of review: This review identifies the clinical complications associated with the design of the current polyproplylene mesh materials used for the treatment of stress urinary incontinence and pelvic organ prolapse. Following on from this, new alternative materials under development for pelvic floor repair are reviewed. Recent findings: It is well accepted that the textile properties of the current polypropylene surgical meshes are not suitable for the pelvic floor environment. This together with the chemical nature of the current mesh leads to complications whenever implanted in the pelvic floor of women. New alternative materials for the repair of the pelvic floor have been developed with properties designed to be more appropriate for the biomechanical requirements and implantation requirements for the pelvic floor to reduce these clinical complications. To support this, these newer materials are being rigorously tested using more appropriate in-vitro regimes and animal models. Summary: This chapter summarizes developments in the design of new materials for pelvic floor repair. These are being subjected to preclinical testing to exclude materials, which might fail to work in this dynamic environment by either showing a poor mechanical match to the requirements of the tissue or by provoking sustained inflammation. The hope is that new materials will prove effective without causing the high incidence of unacceptable side-effects currently seen with polypropylene mesh implants.